Physiochemical controls on the formation and stability of atacamite in the soil surrounding the Spektakel mine, Northern Cape Province, South Africa - Le Roux, Stephan Gerhard (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.